A reappraisal of transcriptional regulation by NR5A1 and beta-catenin in adrenocortical carcinoma - Lalli, Enzo (Frontiers in Endocrinology, 2023)
Background Overexpression of the transcription factor NR5A1 and constitutive activation of canonical Wnt signalling leading to nuclear translocation of beta-catenin are hallmarks of malignancy in adrenocortical carcinoma (ACC). Based on the analysis of genomic profiles in H295R ACC cells, Mohan et al. (Cancer Res. 2023; 83: 2123-2141) recently suggested that a major determinant driving proliferation and differentiation in malignant ACC is the interaction of NR5A1 and beta-catenin on chromatin to regulate gene expression. Methods I reanalyzed the same set of data generated by Mohan et al. and other published data of knockdown-validated NR5A1 and beta-catenin target genes, Results Beta-catenin is mainly found in association to canonical T cell factor/lymphoid enhancer factor (TCF/LEF) motifs in genomic DNA. NR5A1 and beta-catenin regulate distinct target gene sets in ACC cells. Conclusion Overall, my analysis suggests a model where NR5A1 overexpression and beta-catenin activation principally act independently, rather than functionally interacting, to drive ACC malignancy.